Stump Ranch Chronicles and Other Narratives - Knight, Rolf (New Star Books, 1977)
Reminiscences of homesteading, railway construction, logging, mining and life in the farming and resource communities of western Canada in the years since1912 by two populist/socialist participants. Accounts markedly different from the usual picture of rural conservatism and quiescence. –Author's summary
OCLC: 924751354